Muscle structure with low- and high-fat diets in well-trained male runners - Hoppeler, H.; Billeter, R.; Horvath, P. J.; Leddy, J. J.; Pendergast, D. R. (International Journal of Sports Medicine, 1999)
Endurance capacity, maximal oxygen uptake capacity (VO2max) and quantitative muscle ultrastructural composition was analyzed in 7 well-trained male runners (mean age 37.1 years, mean VO2max 60 ml/min/kg) after a one month period of a low-fat diet (dietary fat intake 18.4% and a similar period of a high-fat diet (dietary fat intake 40.6%). Between these two interventional periods a washout period of one month was interspersed in which the nutritional fat content was approx. 32%; close to the average American Diet. During all three periods protein content of the nutrition was kept nearly constant at 15%. After the high-fat diet time to exhaustion in the endurance test increased significantly by 21% while VO2max remained unchanged. Muscle mitochondrial volume density remained unchanged while the intramyocellular fat content increased by 60%. Due to large interindividual differences in this variable this difference did not become statistically significant. While some 20% of the mitochondria are located in a subsarcolemmal location, only 10% of the lipid stores are associated with these mitochondria. Less than 2% of the mitochondrial outer surface are in contact with lipid droplets whereas 25-35% of the lipid surface is in contact with mitochondria. None of these variables is significantly altered after a high-fat diet. It is concluded that the change in endurance capacity of the subjects cannot be explained based on the structural changes observed in skeletal muscle tissue. This may be related to methodological problems associated with the determination of intramyocellular fat content.